2004
DOI: 10.1007/s00115-003-1592-4
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological assessment of suboptimal performance: the Word Memory Test

Abstract: Although malingering, suboptimal cognitive performance, and negative response bias represent very problematic confounds in diagnostic work with a number of neurological and some psychiatric illnesses, the evaluation of these tendencies has not yet become common practice in German-speaking countries. Only a limited number of adequately validated instruments are available. The German adaptation of the Word Memory Test (WMT), an internationally renowned test for use in the area of neurocognitive disturbances, is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(20 citation statements)
references
References 13 publications
0
17
0
3
Order By: Relevance
“…(4) If their hypothesis were true, we would find fewer WMT failures in university students undergoing ADHD assessments than in children or adults with a verbal IQ below 75. On the contrary, we actually find that the university students of Sullivan [7] failed the WMT far more often than either adults or children of very low verbal intelligence (Table II) [15]. Does mild TBI really produce cognitive deficits markedly greater than those seen in mentally handicapped adults?…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…(4) If their hypothesis were true, we would find fewer WMT failures in university students undergoing ADHD assessments than in children or adults with a verbal IQ below 75. On the contrary, we actually find that the university students of Sullivan [7] failed the WMT far more often than either adults or children of very low verbal intelligence (Table II) [15]. Does mild TBI really produce cognitive deficits markedly greater than those seen in mentally handicapped adults?…”
Section: Discussionmentioning
confidence: 92%
“…This is consistent with previous research demonstrating that mild mental retardation, by itself, does not impact performance on the WMT effort subtests. Brockhaus & Merten [15] reported that 31 out of 32 institutionalized but testable mentally handicapped adults in Germany were able to pass the WMT using the usual criteria (Table II), showing that low cognitive abilities, in themselves, are not necessarily associated with failure on the WMT. On the contrary, the single group in Table II with the highest levels of education and intelligence were university students, yet they had the highest WMT failure rate of all.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For this reason, different effort indices need to be emphasized, and perhaps new ones developed, for a low IQ population. In this study, the Warrington Recognition Memory Test-Words was effective at low IQ levels, and the limited data available on other forced-choice tests in low IQ groups has frequently been positive with respect to specificity (e.g., Logical Memory Rarely Missed Items Index ¼ 91%, Marshall & Happe, in press; German WMT ¼ 97%, Brockhaus & Merten, 2004; CVLT-2 Recognition ¼ 89%, Marshall & Happe, in press;TOMM ¼ 50-100%, W. R. Drwal, personal communication, August 29, 2005;Graue et al, in press;Kennedy et al, 2005;Hurley & Deal, 2006;Weinborn et al, 2003; Digit Memory Test ¼ 85%, Graue et al, in press). In addition, forced choice scores significantly below chance would not be plausible in any IQ range.…”
Section: Discussionmentioning
confidence: 94%
“…With regard to the Word Memory Test (WMT), Dean et al (2008, p. 709) reported data from Brockhaus and Merten's (2004) study of 32 German adults with ID. According to Dean, Victor, Boone, and Arnold (2008), Brockhaus and Merten obtained an exceptionally high specificity rate of .97.…”
Section: Word Memory Testmentioning
confidence: 98%